A MULTICENTER, BLIND, RANDOMIZED, PLACEBO-CONTROLLED STUDY OF THE SYMPTOM- AND STRUCTURE-MODIFYING EFFET OF ALFLUTOP IN PATIENTS WITH KNEE OSTEOARTHRITIS. REPORT 2: THE ASSESSMENT OF THE STRUCTURE-MODIFYING EFFECT OF THE DRUG - L. I. Alekseeva; E. P. Sharapova; E. A. Taskina; N. V. Chichasova; G. R. Imametdinova; N. A. Shostak; N. G. Pravdyuk; L. N. Denisov (Научно-практическая ревматология, 2014)
Objective. To evaluate the symptom- and structure-modifying effect of Alflutop compared to placebo (PL) in patients with knee osteoarthritis (OA). Material and methods. The study included 90 patients with knee OA (according to the criteria of the Russian Association of Rheumatologists) at the stage 2–3 (according to the Kellgren-Lawrence scale); pain score when walk- ing ≥ 40 mm (assessed using the visual analog scale). All the patients provided an informed consent. The patients were randomly divided into two groups: group 1 (n=45) received an intramuscular injection of 1 mL Alflutop for 20 days with 6-month intervals for 2 years (a total of 4 courses for 2 years); group 2 (n=45) received an injection of PL (iso- tonic sodium chloride solution) in the same way. Ibuprofen at a dose of 600–1200 mg/day was administered as concomitant therapy. To evaluate the structure-modifying effect of Alflutop, X-ray of the knee joint was performed at the beginning and end of the study; the level of biochemical markers (CTX-II and COMP) was determined at the beginning, after 3 months, and at the end of the study. A statistical analysis was performed using the Statistica 10 software package.Results. After the 2-year follow-up, a statistically significant negative trend was detected less frequently in the group of patients treated with Alflutop compared to the PL group (6.1 and 38.4%, respectively). The statistically significant delay in joint space narrowing was observed in patients who received Alflutop in contrast to patients who received PL (the numerical score of the joint space, the Wilcoxon test; p=0.0003). An increase in osteo- phyte size was observed in 72% of the patients receiving PL, and only in 27% of the patients receiving Alflutop (medial and lateral osteophytes of the femoral bone, the Wilcoxon test; p=0.0078; medial and lateral osteophytes of the shin bone, the Wilcoxon test; p=0.0001 and p=0.0039, respective- ly). Augmentation of subchondral osteosclerosis was determined more often in the PL group (the McNemar's test; p=0.0313). The level of the marker of cartilage degradation CTX-II tended to decrease after 3 months of Alflutop therapy, which has persisted until the end of the study. This indicates a decrease in the articular cartilage degradation. In the PL group, the CTX-II level remained unchanged. A tendency to an increase in the level of the marker of cartilage degradation COMP was found in the PL group. Conclusion. Based on double-blind, placebo-controlled, randomized study, the structure-modifying effect of Alflutop in knee OA has been proved. Alflutop delays the radiographic progression of knee OA, joint space narrowing and osteophyte growth, and reduces the degradation of the articular cartilage matrix.